"We Gotta Get Out of this Place": Literary Criticism in the Academic Workplace. (26th April 2019) - Cassuto, Leonard
Abstract: Winfried Fluck's critique of the work of Rita Felski and Caroline Levine argues that the new formalism of these critics does not escape the Foucauldian regime that they seek to surpass. Following from Fluck's observation, I argue that we should view the practice of literary criticism within the straitened academic workplace within which it is produced—and that this is a context we ignore at our own peril. The longstanding employment problems in academia contribute to the patterns that Felski and Levine identify—and in fact may cause them.